2004
DOI: 10.1080/13645700410034093
|View full text |Cite
|
Sign up to set email alerts
|

Current state of ergonomics of operating rooms of Dutch hospitals in the endoscopic era

Abstract: Laparoscopic procedures are mostly performed in operating rooms which have been designed for conventional surgery. The ergonomic layout of these operating rooms is not suited for endoscopic surgery. This study reports on the current state of ergonomics of Dutch operating rooms for laparoscopic surgery. Number of trolleys, presence of ceiling-mounted booms, and number, positioning and size of monitors were recorded. The floor surface of operating rooms and lowest and highest positions of operating tables were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Surgeons’ static pose during minimally invasive operations resulted in increased muscle fatigue, especially in the neck and back [11, 13]. Additionally, insufficient monitor position causes cervical torsion and results in complaints considering the cervical spine and the upper extremities, including the shoulders [19, 20, 23]. Studies have shown that laparoscopic instruments, which are longer than instruments used in open surgery, cause abduction of the arms during manipulation, also resulting in complaints of the neck and shoulders [42, 43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgeons’ static pose during minimally invasive operations resulted in increased muscle fatigue, especially in the neck and back [11, 13]. Additionally, insufficient monitor position causes cervical torsion and results in complaints considering the cervical spine and the upper extremities, including the shoulders [19, 20, 23]. Studies have shown that laparoscopic instruments, which are longer than instruments used in open surgery, cause abduction of the arms during manipulation, also resulting in complaints of the neck and shoulders [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines have led to ergonomic proposals in the operating theatre during minimally invasive surgery. Firstly, two or more monitors should be present, which are adjustable in height to prevent discomfort in the neck [19, 20]. Secondly, special features of endoscopic instruments led to non-ergonomic position of the wrist and fingers and adjusted redesigned instruments should be the preferred choice [18].…”
mentioning
confidence: 99%
“…Consequently, the majority of surgeon strain for these procedures is transmitted to the neck, which is hyperextended to look at the video display while the arms are working at a lower-than optimal height on tables that were initially designed for open procedures. 25 Laparoscopic prostatectomy, however, is quite different, because it requires the surgeon to operate in a craniocaudal (or parallel) axis to the patient. Thus, ports are placed on both sides of the midline and operative work necessitates reaching over the patient and across the midline.…”
mentioning
confidence: 99%
“…Because the current operating tables are originally designed for open surgery, they are not optimal for minimally invasive procedures with regard to ergonomic guidelines. The current operating tables are adjustable in height to between 725 and 1,215 mm [2]. A previous study showed that the discomfort and difficulty ratings were lowest when instruments handles were positioned at elbow height of the surgeon [7].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because operating tables were originally designed for open surgery, they are not optimal for minimally invasive procedures. The operating tables are adjustable in height to between 725 and 1,215 mm [2].…”
mentioning
confidence: 99%